1962
DOI: 10.4039/ent94884-8
|View full text |Cite
|
Sign up to set email alerts
|

The Olfactory Guidance of Flying Insects. IV. Drosophila

Abstract: The upwind guidance of flying insects was considered in a previous paper (Wright, 1958) where a homing mechanism was suggested that did not require visual contact with the ground. The response of Drosophila to attractive scents presented in various ways has now been studied. The results show that visual contact with the ground is in fact essential, and other factors of the guidance system have been clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…melanogaster, as suggested by the anecdotal studies of Wright and colleagues, respond in an apparently qualitatively different fashion from several moth species (besides, perhaps, C. cautella as described above), when exposed to a homogeneous odor plume (Kellogg et al, 1962;Wright, 1964). Under that condition, D. melanogaster consistently exhibited the straightest upwind trajectories that we observed in any treatment, and thus seem to depart from the Baker model for moth flight in that flies' upwind response to an attractive odor does not adapt to constant stimulation in the short term.…”
Section: Odor-mediated Flight In Drosophilamentioning
confidence: 99%
See 2 more Smart Citations
“…melanogaster, as suggested by the anecdotal studies of Wright and colleagues, respond in an apparently qualitatively different fashion from several moth species (besides, perhaps, C. cautella as described above), when exposed to a homogeneous odor plume (Kellogg et al, 1962;Wright, 1964). Under that condition, D. melanogaster consistently exhibited the straightest upwind trajectories that we observed in any treatment, and thus seem to depart from the Baker model for moth flight in that flies' upwind response to an attractive odor does not adapt to constant stimulation in the short term.…”
Section: Odor-mediated Flight In Drosophilamentioning
confidence: 99%
“…A fairly wide range for this parameter has been reported in the moth literature, with a shift to cross-wind flight within 150-220·ms in G. molesta (Baker and Haynes, 1987), 490·ms in Manduca sexta (Willis and Arbas, 1991), 710·ms in C. cautella (Mafra-Neto and Cardé, 1996) or about 1·s in Lymantria dispar (Kuenen and Cardé, 1994). Kellogg et al even suggested a value of about 100·ms for D. melanogaster, based on their anecdotal results (Kellogg et al, 1962). Despite this variability in the timing of initiation, it is interesting that this flight maneuver is shared with the phylogenetically distant Lepidoptera and implies perhaps that the problem of olfactory search is sufficiently universal to often rely on the same search algorithms.…”
Section: Odor-mediated Flight In Drosophilamentioning
confidence: 99%
See 1 more Smart Citation
“…Anecdotal evidence suggests that flying and walking Drosophila produce zigzag movements when approaching an odor, suggestive of cross-wind movement [19]. However, Drosophila can fly upwind in both continuous and pulsed odor streams [20,21], unlike moths which do not fly upwind in a continuous stream. It has also been reported that tethered flying Drosophila will orient into continuous plumes, or plumes pulsed at high frequencies, but not plumes pulsed at low frequencies [22].…”
Section: Chemotaxis Strategies and The Olfactory Landscapementioning
confidence: 99%
“…(1984). The olfactometer tests mainly for optomotor anemotaxis, which is a mechanism whereby Drosophila respond to distant plant odours (Kellogg, Frizel and Wright, 1962;Shorey, 1976).…”
mentioning
confidence: 99%